Type of instructions performed in online teaching and learning - Mufaridah, Fitrotul (Linguistics and Culture Review, 2021)
Teaching and learning has changed and performed new challenge to provide attracting instruct for students to be active in online learning. The way to run the process of teaching and learning are modified. The use of technology in communicating the teaching-learning material is challenging. Different types of instructions motivate different to students to follow the online class activities. The communication delivered through the instructions becomes a key to guide the process of online teaching and learning. How the instructions performed by the teacher create interesting interaction in online learning. So, it is interesting to analyze further how the instructions work to activate the students’ involvement in online teaching-learning. This research is to describe how the types of instructions performed in online teaching and learning based on the implementation of teaching model. The data is collected from documents of lesson instruction design. This research uses qualitative approach to analyze the data. The result of the research is analyzed related to the types of instructions used in processing the learning activites through instructions provided by the teacher. The conclusion found three types of appropriate instructions to motivate and activate students in the process of online teaching and learning.